Direct puncture versus run up cervical myelography with iopamidol: a comparison of side effects, EEG changes and radiographic quality. Issue 10 (October 1983) - Macpherson, P; Teasdale, E; McGeorge, A P
Abstract : A series of cervical myelograms performed by direct puncture resulted in almost identical incidence of side effects, more contrast within the skull, more frequent EEG abnormalities and only slightly better radiographic quality than in a comparable series of patients in whom the contrast was run up from the lumbar region.